Analysis Of Needs And Placement Of Zinc Anode For New Ferry Ship Buildings - Syaifullah, Muh.; Sade, Juswan; Paroka, Paroka (Maritime Park: Journal of Maritime Technology and Society, 2024)
Marine structures (ships, offshore platforms, underwater pipes and other floating structures) in operation are not protected from corrosion. One of the biggest sources of damage to ships is caused by seawater corrosion. Until now, the use of iron and steel as the main materials for shipbuilding is still dominant. Corrosion is a degradation process of a metal due to chemical reactions between the metal and its environment. The aim of this research is how to determine the need for zinc anode and efficient installation distance as well as the costs required in procuring cathodic protection. Cavitation is a factor that often occurs around propellers or propellers. When the propeller or propeller rotates in the water, the low pressure around the surface of the propeller can cause water vapor to form and turn into cavitation bubbles. When these bubbles burst, the erosion effect on the surface of the affected object will quickly corrode. So that the installation of the sacrificial anode at the stern is installed slightly tightly. The method used to control the rate of corrosion is by protecting the steel plate using cathodic protection. Therefore, every ship that is built needs to have zinc anode planning to control the rate of corrosion on the ship's steel plates. The number of zinc anodes required for a new construction ship with a length of 72.76 m, a width of 14 m and a draft height of 3.30 m is 55 with an addition of 30% of the total number at the stern due to the cavitation factor. The design life of the zinc anode protection is 2.5 years with a longated flush mounted (welded type) type s-8, dimensions (300 mm × 150 mm × 25 mm) weighing 8 kg. The installation distance is 3 m and 1.3 m with the installation cost being IDR. 40,530,000.